Ruthenium-Catalyzed C–H Silylation of 1-Arylpyrazole Derivatives and Fluoride-Mediated Carboxylation: Use of Two Nitrogen Atoms of the Pyrazole Group - Mita, Tsuyoshi; Tanaka, Hiroyuki; Michigami, Kenichi; Sato, Yoshihiro (Synlett, 2014)
Carboxylation of 1-arylpyrazole derivatives was developed using a ruthenium-catalyzed ortho silylation in conjunction with fluoride-mediated carboxylation with carbon dioxide. The two nitrogen atoms of pyrazole play crucial roles in promoting ortho silylation via the formation of a five-membered ruthenacycle and in accelerating aryl anion formation by lowering the electron density of the aromatic ring.
Keywords: C–H activation; carbon dioxide; silylation; ruthenium; pyrazole